The pathophysiology of motor fatigue and fatigability in multiple sclerosis - Patejdl, Robert; Zettl, Uwe K. (Frontiers in Neurology, 2022)
Multiple Sclerosis (MS) is a heterogeneous immune mediated disease of the central nervous system (CNS). Fatigue is one of the most common and disabling symptom of MS. It interferes with daily activities on the level of cognition and motor endurance. Motor fatigue can either result from lesions in cortical networks or motor pathways (“primary fatigue”) or it may be a consequence of detraining with subsequent adaptions of muscle and autonomic function. Programmed exercise interventions are used frequently to increase physical fitness in MS-patients. Studies investigating the effects of training on aerobic capacity, objective endurance and perceived fatiguability have yielded heterogenous results, most likely due to the heterogeneity of interventions and patients, but probably also due to the non-uniform pathophysiology of fatiguability among MS-patients. The aim of this review is to summarize the current knowledge on motor fatiguability with special reference to the basic exercise physiology that underlies our understanding of both pathogenesis and treatment interventions.